Prevalence of tuberculosis, HIV/AIDS, and hepatitis; in a prison of Balochistan: a cross-sectional survey - Wali, Ahmad; Khan, Dawood; Safdar, Nauman; Shawani, Zeenat; Fatima, Razia; Yaqoob, Aashifa; Qadir, Aurangzeb; Ahmed, Sultan; Rashid, Hamayun; Ahmed, Bashir; Khan, Shereen (BMC public health, 2019)
Human Immunodeficiency Virus (HIV), Hepatitis, and Tuberculosis (TB) are three primary communicable infections have the likely potential to cause severe morbidity in prison settings. The prison has the most favorable environment for the transmission of infections. We conducted this survey to determine the prevalence and feasibility of rapid diagnostic tests in an active screening of these infectious diseases in prison. This cross-sectional survey conducted in central Jail Gaddani, one of the largest prisons in the Balochistan province of Pakistan. All prisoners, jail staffs, and staff's family members participated. Informed consent obtained from each participant before the screening. Van equipped with digital X-ray linked with Computer-Aided Detection for TB (CAD4TB) software used for testing. Sputum samples tested on Xpert for MTB/RIF assay and blood specimens collected for HIV and hepatitis serology. Diagnosed TB patients enrolled for treatment at Basic Management Unit (BMU), reactive on hepatitis Rapid Diagnostic Tools (RDTs) were referred for further testing and management, while HIV reactive referred to Anti Retro Viral (ARV) center for Anti Retro Viral Treatment (ART). A total of 567 participants offered screening, 63% (356) prisoners, 23% (129) staff's family members, and 14% (82) jail staffs. Among tested 10.3% (58/562) were hepatitis seropositive (Hepatitis-C 41 [7.29%] Hepatitis-B, 16 [2.84%] Hepatitis B&C both, 01 [0.17%]). In reactive participants, 49 were prisoners, 08 were jail staffs, and 01 was the staff's family member. HIV seropositive was 4% (24/566), and all were prisoners. Almost 99% (565/567) screened by digital X-ray, 172 (30%) were with abnormal CAD4TB suggestion (score > 50), out of them sputum of 26% (148) tested on Xpert, and 2% (03) found Mycobacterium tuberculosis Positive (MTB+). A total of five TB patients were detected; out of two were diagnosed clinically. Co-morbidities observed in 15 patients, (01 TB/HIV co-infected, 12 HIV/HCV, 01 HIV/HBV, and 01 HBV/HCV). The high frequency of infectious diseases in prison is alarming. For limiting the transmission of infections among prison and community, immediate steps are needed to be taken for improvement of prisons condition by application of recommended screening protocols at the time of the first entry of prisoners in prisons.